Working class disempowerment: A dialectical analysis - Tawakkol, Lama (AUC Knowledge Fountain, 2017)
Much like all processes, empowerment is dialectical. Rather than being a one-sided attempt, the (dis)empowerment of capital or the working class is governed by the perpetual struggle between them. Building on this, this thesis investigates the relation between both parties to the struggle, examining how workers have been disempowered by capital in our contemporary moment. By specifically focusing on production processes, social relations and mental conceptions, it analyzes workers’ position in the class struggle and outlines opportunities for their organization, stronger resistance and alternatives. The thesis conducts a universal analysis, while drawing on particular examples, to emphasize the similarity in different workers’ experiences, break through dominant fetishisms and enhance the working class’s position in relation to capital and, hence, its prospects for empowerment and liberation.